2022
DOI: 10.1177/02692155221135028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical exercise on fear of falling in patients with stroke: A systematic review and meta-analysis

Abstract: Objective To consolidate the evidence on the effect of physical exercise on fear of falling in individuals with stroke. Data Sources PubMed, CINAHL, Cochrane Database and MEDLINE Methods An extensive database search was conducted to identify the randomised controlled trials that examined the effect of physical exercise on fear of falling post-stroke. Grading of Recommendation, Assessment, Development and Evaluation (GRADE) was used to assess the quality of evidence for each meta-analysis. Results Fourteen tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Regarding the significantly improving effect of applying GDT only in the control group, the patient gained more self-assurance and fall efficacy as a result. This is supported by the results of a recent systematic review that found a substantial overall positive effect of GDT on FoF from six studies included in their systemic review analysis (four showed a significant difference between GDT and control) (16). There was no clear explanation for this decrease in FoF after the GDT application.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Regarding the significantly improving effect of applying GDT only in the control group, the patient gained more self-assurance and fall efficacy as a result. This is supported by the results of a recent systematic review that found a substantial overall positive effect of GDT on FoF from six studies included in their systemic review analysis (four showed a significant difference between GDT and control) (16). There was no clear explanation for this decrease in FoF after the GDT application.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, GDT can preferentially activate self-efficacy, which is a creative capacity that requires the integration of several types of knowledge and skill research, including intellectual, social, and behavioral capacities ( 13 ). Furthermore, verbal encouragement and feedback from the physical therapist during exercise may also promote a sense of balance self-efficacy ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation